Emergency Department Utilization in the U.S. Military Health System. Issue 5 (3rd May 2021) - Dalton, Michael K; Andriotti, Tomas; Matsas, Bridget; Chaudhary, Muhammad Ali; Tilley, Laura; Lipsitz, Stuart; Learn, Peter A; Schoenfeld, Andrew J; Jarman, Molly P; Goralnick, Eric
ABSTRACT: Introduction: Emergency department (ED) utilization represents an expensive and growing means of accessing care for a variety of conditions. Prior studies have characterized ED utilization in the general population. We aim to identify the clinical conditions that drive ED utilization in a universally insured population and the impacts of care setting on ED use and admissions in the U.S. Military Health System. Methods: We queried TRICARE claims data from October 1, 2012, to September 30, 2015, to identify all ED visits for adult patients (age 18-64). The primary presenting diagnoses of all ED visits and those leading to admission are presented with descriptive statistics. Logistic regression was used to identify clinical and sociodemographic factors associated with admission from the ED. Results: A total of 4, 687, 205 ED visits were identified, of which 46% took place in the DoD healthcare facilities (direct care). The most common diagnoses across all ED visits were abdominal pain, chest pain, headache, nausea and vomiting, and urinary tract infection. A total of 270, 127 (5.8%) ED visits led to inpatient admission. The most common diagnoses leading to admission were chest pain, abdominal pain, depression, conditions relating to acute psychological stress, and pneumonia. For patients presenting with 1 of the 10 most common ED diagnoses, those who were seen at a civilian ED were significantly less likely to be admitted (3.4%) compared to direct care facilities (4.1%) in an adjusted logistic regression model (Adjusted Odds Ratio 0.40 [95% CI: 0.40-0.41], P  < .001). Conclusions: Ultimately, we show that abdominal pain and chest pain are the most common reasons for presentation to the ED in the Military Health System and the most common presenting diagnoses for admission from the ED. Among patients presenting with the most common ED conditions, direct care EDs were significantly more likely to admit patients than civilian facilities.